TRANSPARANSI DAN AKUNTABILITAS DALAM PENERAPAN SISTEM KEUANGAN DESA (SISKEUDES) DI DESA BANYUMAS KECAMATAN STABAT KABUPATEN LANGKAT - Hidayani, Sandra; Kamilah, Kamilah; Tambunan, Khairina (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2023)
This research is determining the implementation of the Village Financial System (SISKEUDES) in transparency, accountability, and constraints on village fund management in Banyumas Village, Stabat District, Langkat Regency. The data used in the research are primary data from interviews and secondary data from the Banyumas Village SISKEUDES Application. The results show that the SISKEUDES implementation in the transparency and accountability of Banyumas village fund management, Stabat District, Langkat Regency has been carried out under Permendagri No. 20 of 2018. The SISKEUDES application can facilitate Village Officials in increasing transparency and accountability in the Financial Management Village in Banyumas Village, starting from the planning, implementation, administration, reporting, and accountability stages. But there is still no banner or announcement board regarding Village Financial Management. There are various challenges to using the SISKEUDES Application; Access to the application may fail due to signal interference, inputting taxes might not be possible, and concurrent usage by multiple users may cause errors or inaccessibility.